The Effects of Serotonin in Immune Cells - Herr, Nadine; Bode, Christoph; Duerschmied, Daniel (Frontiers in Cardiovascular Medicine, 2017)
Serotonin (5-Hydroxytryptamine, 5-HT) plays an important role in many organs as a peripheral hormone. Most of the body's serotonin is circulating in the bloodstream, transported by blood platelets and is released upon activation. The functions of serotonin are mediated by members of the 7 known mammalian serotonin receptor subtype classes (15 known subtypes), the serotonin transporter (SERT) and by covalent binding of serotonin to different effector proteins. Almost all immune cells express at least one serotonin component. In recent years, a number of immunoregulatory functions have been ascribed to serotonin. In monocytes/macrophages for example serotonin modulates cytokine secretion. Serotonin can also suppress the release of TNF-α and IL-1β by activating serotonin receptors. Furthermore, neutrophil recruitment and T-Cell activation can both be mediated by serotonin. These are only a few of the known immunomodulatory roles of serotonin that we will review here.